Evaluating Generative Ai Technologies in Transforming Order Fulfillment: Predictive Ai for Personalization and Optimization in E-Commerce - Vijayendra Vittal Rao (International Journal of Computational and Experimental Science and Engineering, 2025)
This study looked at how generative and predictive AI technology could change the way orders are filled in the e-commerce sector. The study looked at how AI-powered technologies affected important performance indicators including delivery time, inventory correctness, customer satisfaction, and customization efficacy by looking at operational data and qualitative insights from three mid-sized e-commerce platforms. The results showed that predictive AI made demand forecasting much better, lowered fulfillment costs, and cut down on stockouts. Generative AI, on the other hand, made customer engagement better by giving them personalized recommendations and interactions. Using all of these technologies together made businesses more efficient and made customers more loyal. The study showed that AI adoption in order fulfillment provided flexible, tailored, and data-driven workflows that could react to quickly changing market conditions, even though the initial integration was difficult.